Implementasi Metode Problem Based Learning Pada Mata Pelajaran Al-Quran dan Hadist Untuk Meningkatkan Hasil Belajar Kognitif dan Penanaman Sikap Peduli Sosial Pada siswa MTs Negeri 1 Sidoarjo: Implementation of Problem Based Learning Methods in Al-Quran and Hadith Subjects to Improve Cognitive Learning Outcomes and Cultivating Social Care Attitudes in Students of MTs Negeri 1 Sidoarjo - Adawiyah, Robiatul (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to find out the application of learning methods of problem base learning to improve learning outcomes and social care attitudes of VIII-D students of MTs Negeri Siodarjo in the Koran and subjects. The research method uses classroom action research (CAR) which is carried out through the stages of cycle I and cycle II. Data collection techniques in research through observation, tests of cognitive learning outcomes and giving questionnaires. The results of the implementation of the problem based learning method for the first cycle were carried out with good criteria and for the second cycle it was carried out with very good criteria. The cognitive learning outcomes of Al-Quran subjects and Hadith for VIII D students in the first cycle reached 88.20% who achieved a score above KKM (minimum completeness criteria) that is set, and in the second cycle reaches 100% that reaches a score above the KKM (minimum completeness criteria). Whereas the students' social care attitude after applying problem based learning learning method in the Al-Qurana and Hadith subjects has a social caring attitude with the category for students of class VIII-D MTS Negeri 1 Sidoarjo.